Mobile-based in-home telerehabilitation compared with in-hospital face-to-face rehabilitation for elderly patients after total hip arthroplasty in China's level 1 trauma center: a noninferiority randomized controlled trial - Zhou, Yang; Lyu, Yiming; Wang, Qiaojie; Ma, Yanhong; Huang, Lihua; Zhang, Xin (Frontiers in Surgery, 2025)
BackgroundTelerehabilitation is gaining popularity in European and American countries, but whether it can be successfully implemented in China still lacks support from clinical studies.ObjectiveThis trial aimed to determine if a home-based telerehabilitation method is clinically noninferior to standard in-hospital face-to-face rehabilitation for elderly patients with total hip arthroplasty (THA) in China.MethodsThis multicenter randomized controlled trial was conducted from January 2021 to June 2022 at The First Rehabilitation Hospital in Shanghai, Shanghai Jiao Tong University affiliated Sixth People's Hospital and Shanghai Tongji University affiliated Tenth People's Hospital. Sixty-four patients were recruited for this two-arm, single-assessor blinded, randomized controlled trial. The participants were randomly assigned to the in-home telerehabilitation group (TELE group) and the in-hospital physical therapist in-person group (PT group). The intervention consisted of a 12-week home-based rehabilitation program with video instructions and remote coaching on a mobile APP (TELE group). The PT group received a standard in-hospital rehabilitation intervention assisted by a physical therapist for one month and outpatient clinic for the next two months. Patients were evaluated at baseline, 4 weeks, and 12 weeks postoperatively employing functional tests (Timed Up & Go test and Berg balance test) and self-reported questionnaires (Hip disability and Osteoarthritis Outcome Score (HOOS) and Short Form 12 (SF-12)).ResultsThere was no significant difference between the two groups for the demographic and clinical characteristics. 61 participants were analyzed (PT group: n = 31, women: 48.4% of participants; TELE group: n = 30, 33.3% of participants) whose median age was 70 and 69 years, in PT group (IQR: 63–73) and TELE group (IQR: 66–72) respectively. At 12 weeks follow-up evaluation, the main differences between the two groups regarding the HOOS gains, adjusted for baseline values, were close to zero (P > 0.05). There was no significant difference in primary and secondary outcome measures between the two groups.ConclusionOur results showed the noninferiority of in-home telerehabilitation and advocated its application as a reliable alternative to in-hospital face-to-face rehabilitation for patients who underwent THA.Clinical Trial Registrationhttps://www.chictr.org.cn/, Chinese Clinical Trial Registry (Number: ChiCTR1900025825).